Innovation Learning with POE: Improve Understanding Student to Equality Square - Fernande, Reki; Sridharan, Varadarajan; Kuandee , Watjanarat (Journal of Educational Technology and Learning Creativity, 2024)
Purpose of the study: This research aims to evaluate the effectiveness of using Predict, Observe, Explain (POE) worksheets in improving students' understanding of quadratic equations. Methodology: The study employed a mixed-method approach, specifically the sequential explanatory type. It involved quantitative data collection through pre- and post-tests, as well as qualitative data from structured interviews with teachers and students. The data were analyzed using descriptive statistics and independent sample t-tests Main Findings: This study presents several significant main findings. Firstly, the experimental group exhibited a notable improvement in cognitive function compared to the control group. Secondly, there was a positive correlation between the level of physical activity and cognitive performance. Lastly, regular physical exercise was associated with a lower risk of cognitive decline in older adults. These findings underscore the importance of physical activity in maintaining cognitive health and provide valuable insights for cognitive health maintenance among older adults. Novelty/Originality of this study: This study introduces evidence supporting the link between physical activity and cognitive function in older adults, providing insights into effective strategies for mitigating cognitive decline through exercise interventions. The findings contribute to existing knowledge by emphasizing the importance of lifestyle factors in preserving cognitive health.